DIFFERENCES IN HYGIENE INDEX OF BRUSHING TEETH WITH HORIZONTAL, ROLL AND FONE'S METHOD IN CHILDREN AGED 9-12 YEARS - Yustina Sriani; Aljufri Aljufri; Yessi Yuzar; Nova Herawati; Lisnayetti Lisnayetti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Brushing your teeth is one way to clean your teeth and take preventive measures in improving dental and oral hygiene. The horizontal technique is a technique that is widely used when brushing teeth. The roll technique is often recommended because it is simple and efficient, while the fone's technique is a proven technique suitable for children because it is easy to do. The purpose of the study was to analyze the hygiene index of brushing teeth with horizontal method, roll and fone's method in children aged 9-12 years. This type of research is an quasi-experimental research with pre-test and post-test designs. There search was carried out by treating respondents and checking the n hygiene index before and after brushing teeth with the horizontal method and the fone's method. The study sample amounted to 45 people with three treatments. The data were analyzed by t-test. The results of the study with paired t-test ? value (0.00<0.05) mean that there is a significant difference between before and after brushing teeth with horizontal, roll and fone's techniques. The average surface of these cleaned teeth is no more than 75% of the tooth surface. The horizontal method averages 51.55%, roll 72.57% and fone's 70.05%. Judging from the increase in hygiene index score, the highest horizontal method increased hygiene index by 34.5%. There is no difference in hygiene index after brushing teeth with horizontal roll and fone's methods. It is recommended to respondents to brush their teeth at least twice in the morning before eating and at night before going to bed with brushing techniques that have been taught, especially fone's. For further researchers, it is recommended to examine the hygiene index with other brushing methods in order to see more effective methods in cleaning all tooth surfaces.